Curriculum Development Model With Gender Equality Paradigm And Empowerment Of Generation Z Female Santri Through Entrepreneurship In East Java Islamic Boarding Schools - Mukodi, Mukodi; Sugiyono, Sugiyono; Fashihullisan, M. (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This research develops a curriculum model with gender equality paradigm for empowering Generation Z female santri through entrepreneurship in East Java Islamic boarding schools. Employing descriptive qualitative research methodology with multi-case study approach (Yin, 2018), this study involved 135 respondents from three pesantren with different typologies: Boarding School (PIP) Tremas, Pacitan (salafiyah/traditional), Islamic Boarding School (PP) Al-Hikam, Malang (khalafiyah/modern), and Islamic Boarding School Foundation (YPP) Darul Ulil Albab, Mojokerto (salafiyah-khalafiyah/hybrid). Data collection techniques utilized triangulation through in-depth interviews, participatory observation, and documentation studies, subsequently analyzed using Atlas.ti9. Findings demonstrate that although 100% of respondents acknowledge the existence of gender materials in pesantren curriculum, implementation remains dominated by conventional narratives that position women in domestic roles. The theoretical foundation integrates Quranic hermeneutics, deconstruction of patriarchal, and critical pedagogy. The developed curriculum model comprises four core components: Gender Reinterpretation Module in Islam (30%), Sharia Entrepreneurship Module (40%), Self-Development and Leadership Module (20%), and Islamic Values Integration Module (10%). Model implementation adapts to pesantren typology through staged approaches: gradual for traditional pesantren, direct integration for modern pesantren, and holistic for hybrid pesantren. This model provides significant contribution to pesantren curriculum transformation that is gender-responsive and relevant to Generation Z characteristics that are digital-native and entrepreneurial